Women’s Struggle for Economic Equality within Patriarchy in Marjorie Barnard`s Short Story, "The Lottery" - Pandey , Pusp Raj (AMC Journal (Dhangadhi), 2024)
This paper explores women's struggle for economic equality within patriarchy. Marjorie Barnard`s short story "The Lottery"(1959) is taken as a primary text to explore the struggle of women against patriarchal systems for their equal economic rights by interpreting the women`s position within their family and society. Women are exploited, oppressed, and deprived of their access to economic space. As a result, women face subordination, and male domination including unequal pay, rights to property and job opportunities. Patriarchy is so powerful it always hinders women and controls their economic domain. Patriarchy rules women both through language and actions. Women are the main victims of patriarchy because females suffer from workplace disparities, less wages and less job opportunities in comparison to males. Women struggle and raise their voice against the existing system of patriarchy for their economic equality as males. Despite this they still face problems in the economic lives of women.